scRNA-seq reveals elevated interferon responses and TNF-α signaling via NFkB in monocytes in children with uncomplicated malaria - Collins M. Morang’a; Riley S. Drake; Riley S. Drake; Riley S. Drake; Riley S. Drake; Vincent N. Miao; Vincent N. Miao; Vincent N. Miao; Vincent N. Miao; Nancy K. Nyakoe; Dominic S. Y. Amuzu; Vincent Appiah; et al. (Experimental Biology and Medicine, 2025)
Malaria causes significant morbidity and mortality worldwide, disproportionately impacting sub-Saharan Africa. Disease phenotypes associated with Plasmodium falciparum infection can vary widely, from asymptomatic to life-threatening. To date, prevention efforts, particularly those related to vaccine development, have been hindered by an incomplete understanding of which factors impact host immune responses resulting in these divergent outcomes. Here, we conducted a field study of 224 individuals to determine host-parasite factors associated with symptomatic malaria “patients” compared to asymptomatic malaria-positive “controls” at both the community and healthy facility levels. We further performed comprehensive immune profiling to obtain deeper insights into differences in response between the pair. First, we determined the relationship between host age and parasite density in patients (n = 134/224) compared to controls (n = 90/224). Then, we applied single-cell RNA sequencing to compare the immunological phenotypes of 18,176 peripheral blood mononuclear cells isolated from a subset of the participants (n = 11/224), matched on age, sex, and parasite density. Patients had higher parasite densities compared to the controls, although the levels had a negative correlation with age in both groups, suggesting that they are key indicators of disease pathogenesis. On average, patients were characterized by a higher fractional abundance of monocytes and an upregulation of innate immune responses, including those to type I and type II interferons and tumor necrosis factor-alpha signaling via NFκB. Further, in the patients, we identified more putative interactions between antigen-presenting cells and proliferating CD4 T cells, and naïve CD8 T cells driven by MHC-I and MHC-II signaling pathways, respectively. Together, these findings highlight transcriptional differences between immune cell subsets associated with disease phenotypes that may help guide the development of improved malaria vaccines and new therapeutic interventions.